Barriers to successful implementation of renewables-based rural electrification - Adriana Valencia; Georg Caspary (Deutsches Institut für Entwicklungspolitik (DIE), 2008)
Among the various options for off-grid rural electrification, renewables-based off-grid electrification holds particular promise due to the double dividends it offers: reduction of poverty and of greenhouse gas emissions. Notably, off-grid renewable energy systems can be suitable for applications in remote rural areas where energy consumers are dispersed and have low demand. However, these double dividends are not fully captured if productive uses of electricity are not also put in place, through additional planning and investment. Barriers to implementing renewables-based rural electrification include both entry and project continuation barriers that have so far led to project performance below expectations. The most important lessons from our barriers analysis are firstly the need for proper information about renewable energy to decision-makers, as well as about least-cost options and development-environment double dividends to be had from these technologies. Secondly, there is a need to tailor electrification efforts to communities' needs and capacities.
Keywords: 330